Mranʻ mā Nuiṅʻ ṅaṃ ʼa nokʻ mrokʻ puiṅʻʺ ʼA loṅʻʺ toʻ Kassapa samuiṅʻʺ mhatʻ tamʻʺ - ʼOṅʻ Sinʻʺ, Ūʺ (Ūʺ ʼOṅʻ Sinʻʺ : Phranʻʹ khyī rā ṭhāna Vimutti Yuga Cā pe, 1972)
History and description of ʼA loṅʻʺ toʻ Kassapa, Buddhist shrine in Chindwin, Burma.